Post-Translational Regulation of Cathepsin B, but not of Other Cysteine Cathepsins, Contributes to Increased Glioblastoma Cell Invasiveness In Vitro - Gole, Boris; Durán Alonso, María Beatriz; Dolenc, Vincenc; Lah, Tamara (Pathology oncology research, 2009)
Cells that migrate away from a central tumour into brain tissue are responsible for inefficient glioblastoma treatment. This migratory behaviour depends partially on lysosomal cysteine cathepsins. Reportedly, the expression of cathepsins B, L and S gradually increases in the progression from benign astrocytoma to the malignant glioblastoma, although their specific roles in glioma progression have not been revealed. The aim of this study was to clarify their specific contribution to glioblastoma cell invasion. The differences between the matrix invading cells and non-invading core cells from spheroids derived from glioblastoma cell culture and from glioblastoma patients’ biopsies, and embedded in type I collagen, have been studied at the mRNA, protein and cathepsin activity levels. Analyses of the two types of cells showed that the three cathepsins were up-regulated post-translationally, their specific activities increasing in the invading cells. The cystatin levels were also differentially altered, resulting in higher ratio of cathepsins B and L to stefin B in the invading cells. However, using specific synthetic inhibitors and silencing strategies revealed that only cathepsin B activity was involved in the invasion of glioblastoma cells, confirming previous notion of cathepsin B as tumour invasiveness biomarker. Our data support the concept of specific roles of cysteine cathepsins in cancer progression. Finally the study points out on the complexity of protease regulation and the need to include functional proteomics in the systems biology approaches to understand the processes associated with glioma invasion and progression.